Activation of Penile Proadipogenic Peroxisome Proliferator-Activated Receptor 𝛾 with an Estrogen: Interaction with Estrogen Receptor Alpha during Postnatal Development - Mahmoud M. Mansour; Hari O. Goyal; Tim D. Braden; John C. Dennis; Dean D. Schwartz; Robert L. Judd; Frank F. Bartol; Elaine S. Coleman; Edward E. Morrison (PPAR Research)
Exposure to the estrogen receptor alpha (ER𝛼) ligand diethylstilbesterol (DES) between neonatal days 2 to 12 induces penile adipogenesis and adult infertility in rats. The objective of this study was to investigate the in vivo interaction between DES-activated ER𝛼 and the proadipogenic transcription factor peroxisome proliferator-activated receptor gamma (PPAR𝛾). Transcripts for PPARs 𝛼, 𝛽, and 𝛾 and 𝛾1a splice variant were detected in Sprague-Dawley normal rat penis with PPAR𝛾 predominating. In addition, PPAR𝛾1b and PPAR𝛾2 were newly induced by DES. The PPAR𝛾 transcripts were significantly upregulated with DES and reduced by antiestrogen ICI 182, 780. At the cellular level, PPAR𝛾 protein was detected in urethral transitional epithelium and stromal, endothelial, neuronal, and smooth muscular cells. Treatment with DES activated ER𝛼 and induced adipocyte differentiation in corpus cavernosum penis. Those adipocytes exhibited strong nuclear PPAR𝛾 expression. These results suggest a biological overlap between PPAR𝛾 and ER𝛼 and highlight a mechanism for endocrine disruption.